Perceived supernatural support heightens battle confidence: a knife combat field study - Holbrook, Colin (Religion, brain & behavior, 2020)
Religiosity has been historically linked with propensities for both antisocial aggression and prosocial bravery, and prior research employing indirect measures affirms that envisioning the support of supernatural agents promotes confidence in engaging in violent conflict. Here, we provide the first test of this hypothesis within a realistic combat paradigm (i.e., simulated knife fighting). We primed the presence of supernatural aid and collected measures of trait religiosity as well as political orientation, which typically covaries with religiosity and has been similarly linked with battle confidence in prior research. Consistent with predictions, participants evinced greater confidence in their own performance in an imminent knife battle following a guided visualization exercise analogous to prayer summoning supernatural aid. Moreover, individual differences in trait religiosity comparably predicted battle confidence, an effect that was not accounted for by covarying differences in political orientation, which also predicted battle confidence if analyzed independently of religiosity. Against expectations, we observed limited effects of the visualization manipulation or religiosity, and no effect of political orientation, on coalitional confidence in the groups participants fought alongside. These results, derived from unusually valid methods, are discussed as they extend prior research on the confidence-enhancing effects of perceived supernatural support.